2022
DOI: 10.3389/fspas.2022.957223
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between interhemispheric asymmetries in polar ionospheric convection and the magnetic field line footpoint displacement field

Abstract: Polar electrodynamics is largely controlled by solar wind and magnetospheric forcing. Different conditions can make plasma convection and magnetic field disturbances asymmetric between hemispheres. So far, these asymmetries have been studied in isolation. We present an explanation of how they are linked via displacements of magnetic field line footpoints between hemispheres, under the assumption of ideal magnetohydrodynamics. This displacement has so far been studied only on a point by point basis; here we gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In our study we make V 0 vary within that range in order to reproduce the balance between corotation and return flow for various geomagnetic conditions. As for the corotation speed V corotation , which only varies with geographic latitude, we set it to an approximate value of 158 m/s at 70° MLat (Laundal et al., 2022). By choosing a latitude typically within the auroral region, we ensure that the estimated corotation speed corresponds to its value in the magnetospheric PS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we make V 0 vary within that range in order to reproduce the balance between corotation and return flow for various geomagnetic conditions. As for the corotation speed V corotation , which only varies with geographic latitude, we set it to an approximate value of 158 m/s at 70° MLat (Laundal et al., 2022). By choosing a latitude typically within the auroral region, we ensure that the estimated corotation speed corresponds to its value in the magnetospheric PS.…”
Section: Discussionmentioning
confidence: 99%
“…We assume a dipole magnetic field with mean magnetic field B 0 = 30 μT. In this example, we have transformed the electric potential and velocity field to an inertial frame by adding corotation (Laundal et al, 2022b). The decay factor, β, is set to 1/(3 h), i.e., the plasma decay factor is such that it takes 3 h for the plasma to decay by factor 1/e.…”
Section: Example: Solving the 2d Continuity Equationmentioning
confidence: 99%
“…Several other factors could contribute to the differences in the ionospheric electric potential between the northern and southern hemispheres. A previous study has shown that the mismatch in the ionospheric potential could come from the distortion of the geomagnetic field that creates the displacement in the ionospheric footprint (Laundal et al., 2022). Some other studies have also been dedicated to estimating the accuracy of the Tsyganenko model in terms of magnetic conjugacy and magnetic field vectors (Ganushkina et al., 2013; Němec & Kotková, 2021).…”
Section: Introductionmentioning
confidence: 99%